Implementasi Google Form dalam Mengevaluasi Pembelajaran Akidah Akhlak Kelas XI MAN 10 Jombang - Yunizhar, Laili; Diyyanah, Shofiyatud; Mathoriyah, Lailatul (ISLAMIKA, 2024)
Implementation of Google Forms as an assessment medium for learning moral beliefs in class XI MAN 10 Jombang. Targeting the views of teachers and students, the research carried out aims to determine the efficiency and effectiveness, challenges, benefits, and advantages and disadvantages of using Google Forms in assessing the learning of Aqidah Akhlak. Qualitative methods are used to gain in-depth understanding through observation, documentation and interview data collection techniques with teachers involved in the evaluation as well as students who take part in the assessment process using Google Form. The results of the data analysis provide a detailed picture of the application of this tool, increasing understanding of how Google Forms can make the benefits of an efficient and effective solution for evaluating learning in the field of moral belief studies in the classroom. The findings of this research can contribute to the development of technology-based learning practices which were previously manual using paper answer sheets (LJK). The implications of this research are that it can provide practical guidance for developing evaluation methods that are effective and responsive to the needs of students at the educational level.